Validation of cable speedometer for butterfly evaluation - Morouco, P.; Lima, A. B.; Semblano, P.; Fernandes, D.; Goncalves, P.; Sousa, F.; Fernandes, R.; Barbosa, T.; Correira, M. V.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
Getting fast results from the evaluation of swimmers is one of the most important goals to achieve with technological development in the field. The purpose of this study was to validate a real-time velocimetric device (speedometer) through the comparison of their results with Computer assisted videogrametry. The sample included 7 international level swimmers (3 females and 4 males). Each swimmer performed four 25m trials, two at 200m race pace and two at 50m race pace. For each trial, two stroke cycles were studied, resulting on a total of 28 cycles analysed. Hip v(t) curves obtained from speedometer and videogrametry were compared, as well as the speedometer hip curve with the one of the centre of mass (CM). The higher mean correlation obtained was between vhip1 and vhip2 (0.955±0.028), followed by vhip1 with vCM (0.920+0.049). The lower correlation was vhip2 vs. VCM (0.878±0.053). It was concluded that the speedometer is a reliable, fast and Interactive tool for training advice.